Application of the end-of-life demands card game and mindfulness-based cancer recovery program for reducing negative emotion in patients with advanced lung cancer: a randomized controlled trial - Luo, Xian; Miao, Xiaoju; Ding, Nana; Fu, Zhongmin; Wang, Xiaowen; Li, Yonghong (Frontiers in Psychology, 2025)
BackgroundLung cancer is the leading cause of cancer-related deaths globally and the most common type of cancer in China, posing significant health and socio-economic challenges. Despite the effectiveness of psychological interventions for death anxiety, discussions around death are often avoided in China due to cultural taboos and neglect of end-of-life care.PurposeThis study aimed to explore the effectiveness of the self-designed end-of-life demands card game (ELDCG) and mindfulness-based cancer recovery program (MBCR) programs in alleviating death anxiety, anxiety, depression, and stress in patients with advanced lung cancer.MethodsThis was a randomized, single anonymized study. We randomly assigned 77 patients into two groups: the intervention group (38 patients) and the control group (39 patients). Routine health promotion was implemented in the intervention group, along with the ELDCG combined with the MBCR program, while the control group only received routine health promotion. The intervention lasted for 6 weeks. The intervention group completed the ELDCG within the first week, and the MBCR was completed during the remaining 5 weeks. The primary outcome was the Templer’s Death Anxiety Scale (T-DAS) score, and the secondary outcomes were the Hospital Anxiety and Depression Scale (HADS) score, the score on the Chinese version of the Perceived Stress Scale (CPSS), and frequency of selection in the ELDCG. The assessment results of these scales were collected both before the intervention began and after the 6-week intervention period. The frequency of card selections was recorded after the ELDCG.ResultsAfter implementing the 6-week ELDCG and MBCR program, the intervention group showed significantly lower scores than the control group in death anxiety (p < 0.001), anxiety (p < 0.001), depression (p < 0.001), and stress (p < 0.001). The card with the highest selection frequency (13 times) was “I need the right to choose treatment options and understand the expected outcomes.”ConclusionThe ELDCG might assist patients in emotionally coming to terms with death, while the MBCR offered potential strategies for managing stress. Together, they seemed to alleviate death anxiety and negative emotions by addressing these psychological factors, which in turn improves patients’ ability to manage their illness. This improvement not only enhances their quality of life but also helps prevent the unnecessary consumption of healthcare resources, thus alleviating some of the financial strain on the healthcare system. Future research should assess the long-term effects and explore broader applications for terminally ill patients.Clinical trial registrationhttps://clinicaltrials.gov/, identifier ChiCTR2400081628.